Synthesis of Single-Atom Catalysts Through Top-Down Atomization Approaches - Zhang, Aijing; Zhou, Mingzheng; Liu, Siyuan; Chai, Maorong; Jiang, Shengjuan (Frontiers in Catalysis, 2021)
Single atom catalysts (SACs) have been emerged as a hot research area in recently years, and have been intensively investigated in energy storage and conversion. The synthesis of SACs has been significantly advanced due to the enormous efforts devoted into the area. Atomization, contrary to other methods, is a very attractive and innovative top-down approach to achieve high density supported active sites with outstanding stabilities. However, few attentions have been paid to this area despite there are significant advances achieved in the past two years. In this short review, we detailly discussed the latest advancement of atomization for SACs synthesis and highlight the advantages and opportunities.